Partisipasi Masyarakat dalam Musyawarah Perencanaan Pembangunan di Kecamatan Padang Bolak - Nurganti Manik; Adam Adam; Isnaini Isnaini (Mahesa Research Center, 2022)
Sub-district Musrenbang is a forum for deliberation among stakeholders to discuss and agree on steps for handling priority activity programs listed in the Proposed List of Sub-District Development Activity Plans that are integrated with district/city development priorities in the District. The purpose of this paper is to analyze Community Participation and its constraints in Community Participation in the Development Planning Musrenbang in Padang Bolak District. The method used is descriptive qualitative, with data collection techniques to be carried out on data sources. Data collection in this research is using primary data and secondary data. The results showed that the Musrebang in Padang Bolak District, North Padang Lawas Regency has been carried out every year. However, in its implementation, the presence and participation of the community is still considered very lacking. Furthermore, there was a feeling of disappointment expressed by the community over the implementation of the District Musrenbang. The level of community participation in the District Musrenbang is very low, so the activities of holding the District Musrenbang in Padang Bolak are only a formality. Obstacles in the implementation of the District Musrenbang in Padang Bolak are the lack of clarity in communication and socialization related to the Musrenbang, inadequate human resources, limited budget and authority, and the lack of incentives for Musrenbang organizers.